2018
DOI: 10.4236/crcm.2018.77039
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Disease Stabilization and Tolerability in a Nuclear Protein in Testis Midline Carcinoma Patient Treated with Dual Histone Deacetylase and Phosphoinositide 3-Kinase Inhibitor CUDC-907

Abstract: Introduction: Nuclear protein in testis midline carcinoma (NMC) is a rare and extremely aggressive carcinoma (median survival < 7 months) with no effective treatment options. CUDC-907 is a novel small molecule inhibitor of histone deacetylase (HDAC) and phosphoinositide 3-kinase (PI3K) enzymes currently being investigated in multiple tumor types, including NMC. Case Report: A 61-year old female NMC patient enrolled on study CUDC-907-102 (NCT02307240) after rapidly progressing through two prior treatments. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, multimodality protocols including aggressive complete surgical resection followed by postoperative radiotherapy and/or chemoradiotherapy are usually advocated. Clinical trials of bromodomain and extraterminal motif (BET) inhibitors [ 20 ] and histone deacetylase inhibitors (HDACis) [ 21 ] are currently underway, and preliminary results are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multimodality protocols including aggressive complete surgical resection followed by postoperative radiotherapy and/or chemoradiotherapy are usually advocated. Clinical trials of bromodomain and extraterminal motif (BET) inhibitors [ 20 ] and histone deacetylase inhibitors (HDACis) [ 21 ] are currently underway, and preliminary results are promising.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Munster et al. [67] reported a case of NUT carcinoma patients treated with CUDC-907 after two previous treatments with a long-term stable disease of more than 32 months. The literature suggested that CUDC-907 was most effective against NUT carcinoma cells among MYC-targeted drugs (including BET and HDAC inhibitors), followed by panobinostat (an HDAC inhibitor) and AZD5153 (a divalent BET inhibitor) [65] .…”
Section: Therapy Strategiesmentioning
confidence: 99%
“…HDAC inhibition potently suppresses MYC expression at the transcriptional level, while PI3K inhibition results in enhanced ubiquitin-mediated MYC protein degradation at the post-translational level. Munster et al reported a case of prolonged disease stabilization for over 32 months in an NMC patient treated with CUDC-907 after two prior treatments 55…”
Section: Therapeutic Management: From Orphan To Target Diseasementioning
confidence: 99%